Perkembangan Pemanfaatan Feromon untuk Pengendalian Hama Lepidoptera The Development of Pheromone Use to Control Lepidoptera Pests - Andes Triani; Lidya Karlina; M Bagas Tiyantara; Rian Adrian; Raudhatul Fatricia; Yusi Ananda; Chandra Irsan (Seminar Nasional Lahan Suboptimal, 2021)
Triani A, Karlina L, Tiyantara MB, Adrian R, Fatricia R, Ananda Y, Irsan C. 2021. Perkembangan Pemanfaatan Feromon untuk Pengendalian Hama Lepidoptera di Indonesia. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-9 Tahun 2021, Palembang  20 Oktober 2021. pp. 202-208.  Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI). This review was aimed to collect data and information about the development of pheromone use to control lepidoptera pests. The method of the article was reviewing some literatures and then being developed for easy understanding. Pheromone had discovered more than five decades ago and continue to develop. The pheromone used usually as a mass trap or mating disruption. The pheromone used could press the natality of lepidoptera pests. Some pheromones which already been licensed in Indonesia such as fero-exi, fero-grayak, fero-PBPK, fero-lanas, fero-ostri. Until now the development of pheromone use still under development. In conclusion, the use of pheromone has an effective result on controlling Lepidoptera pests and until now, the use of pheromone is still under development.